Improving Students Writing Skills Through Picture-Based Dictation Method: A Creative Approach - Septita Puteri Namirta; Syamsu T; Nurhikmah; Buhari; Sam Hermansyah (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
This study aims to examine the improvement of students’ writing skills through the picture-based dictation method and to explore students’ responses to this method. The main issue addressed is students’ difficulties in composing descriptive texts. This study employs a quantitative approach with an experimental design applied to eighth-grade students, A class. aThe results indicate a significant improvement in students’ writing skills, with an average score increase of 18.78 (from 69.22 to 88.00). Based on the Paired Sample T-test, the calculated t-value (6.302) is greater than the critical t-value (2.056), indicating that this method significantly improves students’ writing in terms of content, grammar, vocabulary, and organization. Students’ responses to this method were highly positive, with an acceptance rate of 96.34%. The integration of audio and visual elements proved to facilitate students in generating ideas and boost their confidence in writing English. It can be concluded that the picture-based dictation method is an effective creative approach to improving students’ learning outcomes and motivation.